Opportunities and constraints for production and income growth in rural Myanmar: Inter-regional variations in the composition of agriculture, livelihoods, and the rural economy - Belton, Ben; Cho, Ame; Filipski, Mateusz J.; Goeb, Joseph; Lambrecht, Isabel B.; Mather, David; Win, Myat Thida (International Food Policy Research Institute, 2021)
This working paper synthesizes findings from four large household and community surveys in Myanmar, each covering a major agro-ecological zone, to evaluate inter-regional variations in the composition of agriculture, livelihoods, and the rural economy, and prospects for production and income growth.